Keeping time on the plant-pathogen arms race : a role for the plant circadian clock in immune response - Bhardwaj, Vaibhav (Department of Molecular and Cell Biology, 2014)
In this study, Arabidopsis thaliana (Arabidopsis) in the Columbia-0 (Col-0) background showed time-of-day variation in susceptibility to the plant-pathogen Pseudomonas syringae DC3000 pathovar tomato (P. syringae DC3000) when infected under constant light and temperature conditions. Wild type plants showed least susceptibility at circadian time (CT) 26 and 50, which correspond to "subjective" morning. Plants were most susceptible when infected at CT42 and CT66, "subjective" night.